Regional differences and convergence of land use efficiency towards carbon neutrality in China’s Yangtze river economic belt - Wang, Kang; Wang, Yifei; Zhang, Jining (Frontiers in Environmental Science, 2025)
Beyond traditional carbon reduction approaches, vegetation carbon sinks play a critical role in advancing carbon-neutral urban development. This study refines the evaluation framework for land use efficiency (LUE) by incorporating regional carbon balance, and applies a global super-efficiency epsilon-based measure (EBM) model to assess LUE in 69 cities across the urban agglomerations of the Yangtze River Economic Belt (YREB) from 2005 to 2020. To examine regional disparities, the Dagum Gini coefficient and kernel density estimation are utilized, while spatial convergence models are employed to explore the dynamic evolution of LUE. The results reveal a U-shaped temporal trend in LUE across the YREB, alongside significant spatial heterogeneity among agglomerations. Inter-regional disparities and transvariation intensity are the main contributors to spatial differences, whereas intra-regional disparities have narrowed over time, particularly in the middle reaches of the Yangtze River—with the exception of the Chengdu-Chongqing region. Spatial convergence analysis further indicates significant absolute and conditional convergence within each agglomeration. These findings suggest that policy efforts to enhance LUE in the YREB should be tailored to the specific regional contexts of economic development, industrial structure, fiscal capacity, and business environment.